1990
DOI: 10.1139/v90-310
|View full text |Cite
|
Sign up to set email alerts
|

An asymmetric synthesis of 2-amino-6,7-dihydroxy-1,2,3,4-tetrahydronaphthalene (ADTN)

Abstract: An asymmetric synthesis of 2-amino-6,7-dimethoxy -1,2,3,4-tetrahydronaphthalene, which can be converted to the title compound by a literature procedure, is described. The synthesis, starting from 2-amino-4,5-dimethoxybenzoic acid and the acrylate of S-methyl lactate, was accomplished in eight steps in 11% overall yield and >97% optical purity.Key words: o-quinodimethanes, Diels-Alder, asymmetric, cycloaddition, induction, diastereoselective, ADTN. Chem. 68, 2028Chem. 68, (1990. On dCcrit une synthkse asymktr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…For all cycloadducts H1 appear between 4.6 and 5.2 ppm (in CDCl,) and endo (cis-1,2) coupling constants, J,,, are 2-5 Hz, while exo (trans-1,2) coupling constants are 7-12 Hz (for previous examples see refs. [2][3][4][5][6]17). The results of the product study are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For all cycloadducts H1 appear between 4.6 and 5.2 ppm (in CDCl,) and endo (cis-1,2) coupling constants, J,,, are 2-5 Hz, while exo (trans-1,2) coupling constants are 7-12 Hz (for previous examples see refs. [2][3][4][5][6]17). The results of the product study are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The solution was dried (MgS04) and evaporated, giving a yellow oil (2.99 g, 42%) that crystallized on standing. Flash chromatography on silica (eluent 20% ethyl acetate/ hexanes) yielded a colourless solid (1.74 g, 24%) a sample of which was crystallized from ethyl acetate/hexanes; mp 62-63°C; ir (CH?C12): 1709 cm-l; 'H nrnr (60 MHz, CDCl,) 6 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since recrystallization and CC failed to give pure 15, the crude product was used without further purification in the next step. (17). In a 100-ml flask were placed Pd · C (80 mg) and 16 (1.00 g, 2.94 mmol) in MeOH (50 ml) and CHCl 3 (3 ml), and a balloon filled with H 2 gas (3 l) was fitted to the flask.…”
Section: Experimental Partmentioning
confidence: 99%
“…As expected, the reaction with Na in liquid NH 3 took place on the electron-deficient ring of 14, giving rise to the carboxylic acid 15 in high yield (90%; Scheme). Next, 15 was transformed into the carbamate 16 by applying a literature procedure described for the synthesis of 6,7-ADTN [13] [17]: reaction of 15 with diphenylphosphoryl azide in the presence of Et 3 N via Curtius rearrangement, followed by treatment with benzyl alcohol, afforded 16 in high yield (88%). Hydrogenolysis of 16 in MeOH in the presence of CHCl 3 then afforded pure 17, which was finally demethylated to the hydrobromide 18 with 48% HBr, as previously described for the synthesis of 5,6-ADTN [8].…”
mentioning
confidence: 99%